POTENSI LICHEN SEBAGAI SUMBER BAHAN OBAT: SUATU KAJIAN PUSTAKA - SEPTIANA, ERIS (Jurnal Biologi Udayana; Vol 15 No 1 (2011): Jurnal Biologi, 2011)
Lichen is a plant with many benefits. Its abundant existence in an area may indicate that air pollution levels are still low. Besides as indicator of air quality, lichen is also used as traditional medicine. Until present time, application of lichens for arthritis, constipation, chemotherapy, external wound, microbial infection, worm and infestation are still done in some countries. It is due to active chemical compounds contain in lichen that has activities as antibacterial, antifungal, antiviral, antitumor, anticancer, antioxidant, anti-inflammatory, antiprotozoa, analgesic and antipyretic, and anthelmintic. With its potential and efforts to provide sustainable materials, lichen has good prospect to be developed become modern medicine.
Keywords: lichen; antiviral; anticancer; antiprotozoa; analgesic